Exploring the feasibility of subliminal priming on web platforms - Caraban, Ana (2022)
Despite the initial premise of behavior change tools, recent work has questioned their efficacy over the long term. Many of these technologies rely on a “one-size fits all” strategy – self-monitoring – to foster behavior change. However, individual’s capacity to change their behaviors depends on their ability and motivation for self-regulation. We explore a different approach to persuasive technology design and investigate how subtle influences falling outside conscious awareness can instinctively motivate behaviors. Subliminal priming has the potential to influence people's attitudes and behaviors, without relying on people’s will to engage with the process. Yet, little research has studied it effectiveness encouraging behavior change outside a laboratory setting. In this paper we explore the feasibility of subliminal priming on web-platforms. We present an in the wild study where 12 participants were exposed to subliminal cues to motivate water intake while they browsed on the web. This paper contributes with a practical application of subliminal priming in the field of behavior change as well as design implications for future research.